Ub-POD: A Ubiquitin-Specific Proximity-Dependent Labeling Technique to Identify E3 Ubiquitin Ligase Substrates in Human Cells - Urbi Mukhopadhyay; Sophie Levantovsky; Christian Behrends; Sagar Bhogaraju (Bio-Protocol)
Ubiquitination is a post-translational protein modification that regulates a vast majority of processes during protein homeostasis. The covalent attachment of ubiquitin is a highly regulated process carried out by the sequential action of the three enzymes E1, E2, and E3. E3 ligases share a dual function of 1) transferring covalently attached ubiquitin from the catalytic cysteine of E2 (E2~Ub) to the substrate and 2) providing substrate specificity. Our current knowledge of their individual substrate pools is incomplete due to the difficult capture of these transient substrate–E3 ligase interactions. Here, we present an efficient protocol that enables the selective biotinylation of substrates of a given ubiquitin ligase. In brief, the candidate E3 ligase is fused to the biotin ligase BirA and ubiquitin to a biotin acceptor peptide, an Avi-tag variant (-2) AP. Cells are co-transfected with these fusion constructs and exposed to biotin, resulting in a BirA-E3 ligase-catalyzed biotinylation of (-2) AP-Ub when in complex with E2. As the next step, the biotinylated (-2) AP-Ub is transferred covalently to the substrate lysine, which enables an enrichment via denaturing streptavidin pulldown. Substrate candidates can then be identified via mass spectrometry (MS). Our ubiquitin-specific proximity-dependent labeling (Ub-POD) method allows robust biotinylation of the ubiquitylation substrates of a candidate E3 ligase thanks to the wild-type BirA and biotin acceptor peptide fused to the E3 and Ub, respectively. Because of the highly Ub-specific labeling, Ub-POD is more appropriate for identifying ubiquitination substrates compared to other conventional proximity labeling or immunoprecipitation (IP) approaches.